14th International Conference on Soft Computing Models in Industrial and Environmental Applications (SOCO 2019) : Seville, Spain, May 13-15, 2019, Proceedings /: Seville, Spain, May 13-15, 2019, Proceedings. ([2020]) - Unknown
No abstract available